A new species and records of the genus Amphichroum Kraatz, 1857 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from Sichuan, China - Shavrin, Alexey V. (Zootaxa, 2019)
The omaliine genus Amphichroum Kraatz, 1857 includes 25 species distributed in the Holarctic Region, thirteen species of which are known from China and Tibet (Shavrin & Smetana 2018). This paper presents description of a new species of Amphichroum collected in Huanglong Shan range in Sichuan. Besides that, records of two species of the genus from the same province are provided.